Customs protection of the Belarusian part of the western border of the USSR in 1944 – early 1950s - Ostroga, Victor A. (Journal of the Belarusian State University. International Relations, 2019)
The restoration of the customs guards on the Belarusian part of the state border of the USSR in the period from 1944 till the first half of the 1950s is analysed in the article. The author considers the main problems that Soviet policy makers had to deal with to create an efficient customs system: legal, organizational, personnel, material and technical. Special attention is paid to the organisation of counteraction to different types of smuggling in the post-war period. It is concluded that a broad and systematic set of measures aimed at strengthening the customs service allowed to control successfully the movement of goods across the border and to fight against smuggling in the early 1950s.
Keywords: state border; border line; restoration; customs service; customs; customs post; border troops; post-war period; customs control; smuggling